Meteoroid Mass Estimation Based on Single‐Frequency Radar Cross Section Measurements. Issue 9 (3rd September 2021) - Tarnecki, L. K.; Marshall, R. A.; Stober, G.; Kero, J.
Abstract: Both high‐power large aperture radars and smaller meteor radars readily observe the dense head plasma produced as a meteoroid ablates. However, determining the mass of such meteors based on the information returned by the radar is challenging. We present a new method for deriving meteor masses from single‐frequency radar measurements, using a physics‐based plasma model and finite‐difference time‐domain (FDTD) simulations. The head plasma model derived in Dimant and Oppenheim (2017), https://doi.org/10.1002/2017ja023963 depends on the meteoroids altitude, speed, and size. We use FDTD simulations of a radar pulse interacting with such head plasmas to determine the radar cross section (RCS) that a radar system would observe for a meteor with a given set of physical properties. By performing simulations over the observed parameter space, we construct tables relating meteor size, velocity, and altitude to RCS. We then use these tables to map a set of observations from the MAARSY radar (53.5 MHz) to fully defined plasma distributions, from which masses are calculated. To validate these results, we repeat the analysis using observations of the same meteors by the EISCAT radar (929 MHz). The resulting masses are strongly linearly correlated; however, the masses derived from EISCAT measurements are on average 1.33 times larger than those derived from MAARSY measurements. Since this method does not require dual‐frequency measurements for mass determination, only validation, it can be applied in the future to observations made by many single‐frequency radar systems. Plain Language Summary: The material left behind as meteoroids burn up in the upper atmosphere has significant effects on atmospheric chemistry and dynamics. However, the amount of mass deposited by any single meteoroid, and therefore the overall input rate, is difficult to calculate. We present a new method for determining individual meteor masses using radar observations and numerical simulations. We use a physics‐based model of the meteor plasma distribution to simulate the interaction between a radar pulse and a meteor, and calculate observable quantities. Using these simulations, we relate the radar observations to physical characteristics of the meteor, which we then use to estimate the mass. Since this method only requires a single radar observation to calculate a meteor's mass, we apply it to a set of meteors observed at the same time by two radar systems, and compare the results. Key Points: A finite difference time domain (FDTD) model is used to simulate radar observations of meteors Meteor mass estimations are made by combining observed radar cross sections with FDTD simulation results A data set of coincident observations by two radar systems is used to verify the mass estimation procedure